Specific character of translation of official documents from Turkish language into Russian language (Journal of Oriental Studies, 2018)
The article is concerned with the description of development of interstate cooperation between the Republic of Kazakhstan and the Republic of Turkey and also representation and transfer in the Turkish-Russian translation system of official documents. Emergence and development of the concept «business correspondence» and also the role of business correspondence in modern society is considered. The specifics of the translation of official style are defined. The main features and methods of the translation, requirement of development of the translation of official documents from Turkish into Russian are emphasized. In article solutions of problems of specifics of the translation of official documents by the comparative and comparative analysis on the basis of official documents in the Russian and Turkish languages are also covered.